INVOLVEMENT OF TAXES IN ENSURING INNOVATION DEVELOPMENT - Abdikerimova Gulzhanar Imanbaevna; Shakirova Farogat Boltaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstrast:  This article explains the nature of taxes and innovations. Also, the impact of taxes on the provision of innovative development has been thoroughly studied.